# RS Aggarwal Class 7 Solutions Chapter 6 Algebraic Expressions Ex 6D

In this chapter, we provide RS Aggarwal Solutions for Class 7 Chapter 6 Algebraic Expressions Ex 6D for English medium students, Which will very helpful for every student in their exams. Students can download the latest RS Aggarwal Solutions for Class 7 Chapter 6 Algebraic Expressions Ex 6D Maths pdf, free RS Aggarwal Solutions Class 7 Chapter 6 Algebraic Expressions Ex 6D Maths book pdf download. Now you will get step by step solution to each question.

### RS Aggarwal Solutions for Class 7 Chapter 6 Exponents Ex 6D Download PDF

Question 1.
Solution:
(5x + 7) (3x + 4)
= 5x (3x + 4) + 7 (3x + 4)
= 5x x 3x + 5x x 4 + 7 x 3x + 7 x 4
= 15x2 + 20x + 21x + 28
= 15x2 + 41x + 28

Question 2.
Solution:
(4x – 3) (2x + 5)
= 4x (2x + 5) – 3 (2x + 5)
= 4x x 2x + 4x x 5 – 3 x 2x -3 x 5
= 8x2 + 20x – 6x – 15
= 8x2 + 14x – 15

Question 3.
Solution:
(x – 6) (4x + 9)
= x (4x + 9) – 6 (4x + 9)
= x x 4x + x x 9 – 6 x 4x – 6 x 9
= 4x2 + 9x – 24x – 54
= 4x2 – 15x – 54

Question 4.
Solution:
(5y – 1) (3y – 8)
= 5y x 3y – 5y x 8 – 1 x 3y – 8 x (-1)
= 15y2 – 40y – 3y + 8
= 15y2 – 43y + 8

Question 5.
Solution:
(7x + 2y) (x + 4y)
= 7x (x + 4y) + 2y (x + 4y)
= 7x x x + 7x x 4y + 2y x x + 2y x 4y
= 7x2 + 28xy + 2xy + 8y2
= 7x2 + 30xy + 8y2

Question 6.
Solution:
(9x + 5y) (4x + 3y)
= 9x (4x + 3y) + 5y (4x + 3y)
= 9x x 4x + 9x x 3y + 5y x 4x + 5y x 3y
= 36x2 + 27xy + 20xy + 15y2
= 36x2 + 47xy +15y2

Question 7.
Solution:
(3m – 4n) (2m – 3n)
= 3m (2m – 3n) – 4n (2m – 3n)
= 3m x 2m – 3m x 3n – 4n x 2m – 4n x (-3n)
= 6m2 – 9mn – 8mn + 12n2
= 6m2 – 17mn + 12n2

Question 8.
Solution:
(0.8x – 0.5y) (1.5x – 3y)
= 0.8x (1.5x – 3y) – 0.5y (1.5x – 3y)
= 0.8x x 1.5x – 0.8x x 3y – 0.5y x 1.5x – 0.5y x (-3y)
= 1.20x2 – 2.4xy – 0.75xy + 1.5y2
= 1.2x2 – 3.15xy + 1.5y2

Question 9.
Solution:

Question 10.
Solution:

Question 11.
Solution:

Question 12.
Solution:
(x2 – a2) (x – a)
= x2 (x – a) – a2 (x – a)
= x2 x x – x2 x a – a2 x x – a2 (-a)
= x3 – xa – xa2 + a3

Question 13.
Solution:
(3p2 + q2) (2p2 – 3q2)
= 3p2 (2p2 – 3q2) + q2 (2p2 – 3q2)
= 3p2 x 2p2 – 3p2 x 3q2 + q2 x 2p2 – q2 x 3q2
= 6q4 – 9p2q2 + 2p2q2 – 3q4
= 6p4 – 7p2q2 – 3q4

Question 14.
Solution:
(2x2 – 5y2) (x2 + 3y2)
= 2x2 (x2 + 3y2) – 5y2 (x2 + 3y2)
= 2x2 x x2 + 2x2 x 3y2 – 5y2 x x2 – 5y2 x 3y2
= 2x4 + 6xy2 – 5xy2 – 15y4
= 2y4 + xy2 – 15y4

Question 15.
Solution:
(x3 – y3) (x2 + y2)
= x3 (x2 + y2) – y3 (x2 + y2)
= x3 x x2 + x3 x y2 – y3 x x2 – y3 x y2
= x5 + xy2 – xy3 – y5

Question 16.
Solution:
(x4 + y4) (x2 – y2)
= x4 (x2 – y2) + y4 (x2 – y2)
= x4 x x2 – x4 x y2 + y4 x x2 – y4 x y2
= x6 – xy2 + xy4 – y6

Question 17.
Solution:

Question 18.
Solution:
(x2 – y2) (x + 2y)
= x2 (x + 2y) – y2 (x + 2y)
= x2 x x + x2 x 2y – y2 x x – y2 x 2y
= x3 + 2xy – xy2 – 2y3

Question 19.
Solution:
(2x + 3y – 5) (x + y)
= 2x (x + y) + 3y (x + y) – 5 (x + y)
= 2x x x + 2x x y + 3y x x + 3y x y – 5 x x – 5 x y
= 2x2 + 2xy + 3xy + 3y2 – 5x – 5y
= 2x2 + 5xy + 3y2 – 5x – 5y

Question 20.
Solution:
(3x + 2y – 4) (x – y)
= 3x (x – y) + 2y (x – y) – 4 (x – y)
= 3x x x – 3x x y + 2y x x – 2y x y – 4 x x – 4 x (-y)
= 3x2 – 3xy + 2xy – 2y2 – 4x + 4y
= 3x2 – xy – 2y2 – 4x + 4y

Question 21.
Solution:
(x2 – 3x + 7) (2x + 3)
= x2 (2x + 3) – 3x (2x + 3) + 7 (2x + 3)
= x2 x 2x + x2 x 3 – 3x x 2x – 3x x 3 + 7 x 2x + 7 x 3
= 2x3 + 3x2 – 6x2 – 9x + 14x + 21
= 2x3 – 3x2 + 5x + 21

Question 22.
Solution:
(3x2 + 5x – 9) (3x – 9)
= 3x2 (3x – 9) + 5x (3x – 9) – 9 (3x – 9)
= 3x2 x 3x – 3×2 x 9 + 5x x 3x + 5x x (-9) – 9 x 3x – 9 x (-9)
= 9x3 – 27x2 + 15x2 – 45x – 27x + 81
= 9x3 – 12x2 – 72x + 81

Question 23.
Solution:
(9x2 – x + 15) (x2 – 3)
= 9x2 (x2 – 3) – x (x2 – 3) + 15 (x2 – 3)
= 9x2 x x2 – 9x2 x 3 – x x x2 + x x 3 + 15 x x2 – 15 x 3
= 9x4 – 27x2 – x3 + 3x + 15x2 – 45
= 9x4 – x3 – 12x2 + 3x – 45

Question 24.
Solution:
(x2 + xy + y2) (x – y)
= x2 (x – y) + xy (x – y) + y2 (x – y)
= x2 x x – x2 x y + xy x x – xy x y + y2 x x – y2 x y
= x3 – x2y + x2y – xy2 + xy2 – y2
= x3 – y3

Question 25.
Solution:
(x2 – xy + y2) (x + y)
= x2 (x + y) – xy (x + y) + y2 (x + y)
= x3 + xy – xy – xy2 + xy2 + y3
= x3 + y3

Question 26.
Solution:
(x2 – 5x + 8) (x2 + 2)
= x2 (x2 + 2) – 5x (x2 + 2) + 8 (x2 + 2)
= x2 x x2 + x2 x 2 – 5x x x2 – 5x x 2 + 8 x x2 + 8 x 2
= x4 + 2x2 – 5x3 – 10x + 8x2 + 16
= x4 – 5x3 + 2x2 + 8x2 – 10x + 16
= x4 – 5x3 + 10x2 – 10x + 16

Simplify:
Question 27.
Solution:
(3x + 4) (2x – 3) + (5x – 4) (x + 2)
= [3x (2x – 3) + 4 (2x – 3)] + [5x (x + 2) – 4 (x + 2)]
= [3x x 2x – 3x x 3 + 4 x 2x – 4 x 3] + [5x x x + 5x x 2 – 4 x x – 4 x 2]
= [6x2 – 9x + 8x – 12] + [5x2 + 10x – 4x – 8]
= (6x2 – x – 12) + (5x2 + 6x – 8)
= 6x2 – x – 12 + 5x2 + 6x – 8
= 6x2 + 5x2 – x + 6x – 12 – 8
= 11x2 + 5x – 20

Question 28.
Solution:
(5x – 3) (x + 4) – (2x + 5) (3x – 4)
= [5x x x + 5x x 4 – 3 x x – 3 x 4] – [2x x 3x + 2x x (-4) + 5 x 3x + 5x (-4)]
= [5x2 + 20x – 3x – 12] – [6x2 – 8x + 15x – 20]
= (5x2 + 17x – 12) – (6x2 + 7x – 20)
= 5x2 + 17x – 12 – 6x2 – 7x + 20
= 5x2 – 6x2 + 17x – 7x – 12 + 20
= -x2 + 10x + 8

Question 29.
Solution:
(9x – 7) (2x – 5) – (3x – 8) (5x – 3)
= [9x (2x – 5) -7 (2x – 5)] – [3x (5x – 3) -8 (5x – 3)]
= [9x x 2x – 9x x 5 – 7 x 2x – 7 x (-5)] – [3x x 5x – 3x x 3 – 8 x 5x – 8 x (-3)]
= [18x2 – 45x – 14x + 35] – [15x2 – 9x – 40x + 24]
= 18x2 – 45x – 14x + 35 – 15x2 + 9x + 40x – 24
= 18x2 – 15x2 – 45x – 14x + 9x + 40x + 35 – 24
= 3x2 – 59x + 49x + 11
= 3x2 – 10x + 11

Question 30.
Solution:
(2x + 5y) (3x + 4y) – (7x + 3y) (2x + y)
= [2x (3x + 4y) + 5y (3x + 4y)] – [7x (2x + y) + 3y (2x + y)]
= [2x x 3x + 2x x 4y + 5y x 3x + 5y x 4y] – [7x x 2x + 7x x y + 3y x 2x + 3y x y]
= [6x2 + 8xy + 15xy + 20y2] – [14x2 + 7xy + 6xy + 3y2]
= [6x2 + 23xy + 20y2] – [14x2 + 13xy + 3y2]
= 6x2 + 23xy + 20y2 – 14x2 – 13xy – 3y2
= 6x2 – 14x2 + 23xy – 13xy + 20y2 – 3y2
= -8x2 + 10xy + 11y2

Question 31.
Solution:
(3x2 + 5x – 7) (x – 1) – (x2 – 2x + 3) (x + 4)
= [3x2 (x – 1) + 5x (x – 1) – 7 (x – 1)] – [x2 (x + 4) – 2x (x + 4) + 3 (x + 4)]
= [3x2 x x – 3x2 x 1 + 5x x x – 5x x (-1) – 7 x x -7 x (-1)] -[x2 x x + x2 x 4 – 2x x x – 2x x 4 + 3 x x + 3 x 4]
= [3x3 – 3x2 + 5x2 – 5x – 7x + 7] – [x3 + 4x2 – 2x2 – 8x + 3x + 12]
= [3x3 + 2x2 – 12x + 7] – [x3 + 2x2 – 5x + 12]
= 3x3 + 2x2 – 12x + 7 – x3 – 2x2 + 5x – 12
= 3x3 – x3 + 2x2 – 2x2 – 12x + 5x – 12 + 7
= 2x3 – 7x – 5

All Chapter RS Aggarwal Solutions For Class 7 Maths

—————————————————————————–

All Subject NCERT Exemplar Problems Solutions For Class 7

All Subject NCERT Solutions For Class 7

*************************************************

I think you got complete solutions for this chapter. If You have any queries regarding this chapter, please comment on the below section our subject teacher will answer you. We tried our best to give complete solutions so you got good marks in your exam.

If these solutions have helped you, you can also share rsaggarwalsolutions.in to your friends.